High-quality Schistosoma haematobium genome achieved by single-molecule and long-range sequencing - Stroehlein, Andreas J; Korhonen, Pasi K; Chong, Teik Min; Lim, Yan Lue; Chan, Kok Gan; Webster, Bonnie; Rollinson, David; Brindley, Paul J; Gasser, Robin B; Young, Neil D (Oxford University Press, 2019)
Background: Schistosoma haematobium causes urogenital schistosomiasis, a neglected tropical disease affecting >100 million people worldwide. Chronic infection with this parasitic trematode can lead to urogenital conditions including female genital schistosomiasis and bladder cancer. At the molecular level, little is known about this blood fluke and the pathogenesis of the disease that it causes. To support molecular studies of this carcinogenic worm, we reported a draft genome for S. haematobium in 2012. Although a useful resource, its utility has been somewhat limited by its fragmentation. Findings: Here, we systematically enhanced the draft genome of S. haematobium using a single-molecule and long-range DNA-sequencing approach. We achieved a major improvement in the accuracy and contiguity of the genome assembly, making it superior or comparable to assemblies for other schistosome species. We transferred curated gene models to this assembly and, using enhanced gene annotation pipelines, inferred a gene set with as many or more complete gene models as those of other well-studied schistosomes. Using conserved, single-copy orthologs, we assessed the phylogenetic position of S. haematobium in relation to other parasitic flatworms for which draft genomes were available. Conclusions: We report a substantially enhanced genomic resource that represents a solid foundation for molecular research on S. haematobium and is poised to better underpin population and functional genomic investigations and to accelerate the search for new disease interventions. © 2019 The Author(s) 2019. Published by Oxford University Press.